Hyaluronic acid in bronchoalveolar lavage fluid in patients with sarcoidosis: relationship to lavage mast cells. - Bjermer, L (1987)
Hyaluronate (hyaluronic acid), a potential marker for activated pulmonary fibroblasts, appears in increased concentrations in bronchoalveolar lavage fluid from patients with sarcoidosis. The mechanisms underlying fibroblast proliferation are largely unknown but activated alveolar T lymphocytes and macrophages probably play a part; the mast cell is also important for fibroblast proliferation. This study was designed to determine whether there is any association between pulmonary mast cells in lavage fluid, which are known to be increased in patients with sarcoidosis, and signs of pulmonary fibroblast activation. A strong correlation was found between lavage fluid hyaluronate and recovered mast cells (r = 0.72, p less than 0.001). Moreover, mast cell and hyaluronate estimations correlated inversely with lung volume and transfer factor for carbon monoxide, and both indices increased with advancing radiological sarcoid stage. Macrophage and granulocyte counts were normal in lavage fluid from patients with sarcoidosis and were not related to lavage fluid hyaluronate or laboratory signs of the disease in the lungs. Lymphocytes were recovered in increased numbers (p less than 0.001) and were related to the lavage fluid mast cells and hyaluronate. It is concluded that in sarcoidosis release of hyaluronate into the airways is related to the degree of lung disease and to the local inflammatory reaction in the lung as defined by increased numbers of mast cells and lymphocytes in lavage fluid. The findings may reflect a link between the immune system, activation of mast cells, and a pulmonary fibroblast proliferation.